Solusi Mudah Belajar Matematika Tingkat Sekolah Dasar Menggunakan Perangkat Lunak Model MADLC - Usman Ependi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
The subjects of mathematics is essentially a learning process to meet the needs logical thinking in solving the problems in science, technology, and everyday life. The condition of common today is learning mathematics in primary school studied in a very theoretical and mechanistic. In other words, the mathematical concept only emphasizes the aspects of the theory without the implication and application. The learning model like this phenomenon perceived lack of understanding and meaningful, coupled with the lack of opportunity for the students to do exercises reset to a formulation of proof in such materials. The main objective of this study is to develop a mobile software for media learning mathematics courses designed for elementary school students of grade VI. The selection mechanism of Mobile Application Development Lifecycle Model (MADLC) as a model of software development because of two things: it has proved capable of mapping matrix analysis of mobile based application is made, and this framework can also specify the process in the deployment of mobile applications after the development phase is done. Some of the features contributions generated in this study is a list of terms, discover the reference material, as well as doing practice questions